Seroprevalence of varicella antibodies in adults without clinical history of disease - Konrad Silva Büchele; Danusa Ferreira Correa; Mari Tuyama; Alberto dos Santos de Lemos; Marcellus Dias da Costa; Emersom Cicilini Mesquita; Daniel Marinho da Costa; José Cerbino-Neto; Margareth Catoia Varela; Pedro Emmanuel Americano Alvarenga do Brasil; Luciana Gomes Pedro Brandão (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: Varicella in adults and immunocompromised patients can be severe. The clinical diagnosis of varicella has high accuracy and the history of disease has a high positive predictive value for protection. A significant portion of adults, however, cannot remember if they have had varicella, especially older individuals. We conducted a cross-sectional study to determine the seroprevalence of varicella protective antibodies titers in adults with no clinical history of disease, attended at a Reference Center for Special Immunobiologicals and Travel Medicine in Rio de Janeiro (Brazil). Titration of immunoglobulin G (IgG) antibodies to varicella-zoster was determined by chemiluminescence immunoassay. Among 140 adults without history of varicella, 92% had protective antibody titers. We concluded that seroprevalence of varicella-zoster protection was very high in adults with negative history of disease and the use of serology before vaccination reduced significantly unnecessary vaccine and immunoglobulin use.